2019
DOI: 10.1530/erc-19-0058
|View full text |Cite
|
Sign up to set email alerts
|

Tetrac as an anti-angiogenic agent in cancer

Abstract: The thyroid hormones T3 and T4 have emerged as pro-angiogenic hormones with important implications for cancer management. Endogenous circulating hormone levels may help stimulate cancer progression and limit the effectiveness of anticancer therapy, though clinical data remain inconclusive. The capacity of thyroid hormones to modulate angiogenesis is mediated through non-canonical mechanisms initiated at the cell surface receptor integrin αvβ3. This integrin is predominantly expressed on tumour cells, prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 138 publications
(144 reference statements)
0
10
0
Order By: Relevance
“…The main role of thyroid hormone is to promote the metabolism of matter and energy, maintain the body's growth and development, and at the same time regulates angiogenesis. Natural thyroid hormone analogs can affect tumor-associated angiogenesis and are important implications for cancer treatment [43]. One study revealed that advanced glycation end products and their receptors (AGE-RAGE) interactions are associated with prostate cancer and may be enhanced prostate cancer cell proliferation by the PI3K/Akt signaling pathway [44].…”
Section: Discussionmentioning
confidence: 99%
“…The main role of thyroid hormone is to promote the metabolism of matter and energy, maintain the body's growth and development, and at the same time regulates angiogenesis. Natural thyroid hormone analogs can affect tumor-associated angiogenesis and are important implications for cancer treatment [43]. One study revealed that advanced glycation end products and their receptors (AGE-RAGE) interactions are associated with prostate cancer and may be enhanced prostate cancer cell proliferation by the PI3K/Akt signaling pathway [44].…”
Section: Discussionmentioning
confidence: 99%
“…T3 exerts the majority of known thyroid hormone (TH) effects at the tissue and cellular level, including hypothalamic and pituitary negative feedback regulation of the hypothalamuspituitary-thyroid-periphery (HPTP) axis (4)(5)(6). Over the last years, some evidence has been presented that T4 also binds to cell membrane-located ανβ3 integrin receptors which exert rapid signaling via various kinase and intracellular pathways, especially in tumor cells and stem cells (7,8). The T4 metabolite Tetrac, a deaminated side chain metabolite, present in human serum at concentrations similar to those of T3 (3,9) antagonizes such T4 (and also T3) actions at the integrin receptor signaling.…”
Section: Introduction Endogenous Thyroid Hormones and Their Metabolitesmentioning
confidence: 99%
“…In cancer patients, endogenous circulating thyroid hormone levels have been implicated in cancer progression and impairment of anti-cancer therapy, though clinical data remain ambiguous [3]. A more complete understanding of the regulation of cancer progression by thyroid hormones is essential to avoid pitfalls in cancer patient treatment and, besides, possibly exploit it for cancer gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A decade and a half since the discovery of a thyroid hormone binding site on integrin αvβ3, a plethora of downstream effects relevant to tumour biology have been described, including stimulation of tumour cell proliferation and angiogenesis [1][2][3]. This phenomenon is of course undesirable in cancer patients and, indeed, over the past century, several clinical and experimental studies have implicated thyroid hormones in cancer progression [3][4][5][6][7]. Integrin αvβ3 is abundantly expressed on most cancer cells and the growing endothelium associated with tumours, but also on mesenchymal stem cells (MSCs), important progenitors for tumour stromaassociated cell types [8,9].…”
Section: Introductionmentioning
confidence: 99%